Optimal Redistributive Taxation When Individual Welfare Depends Upon Relative Income - Boskin, Michael J.; Sheshinski, Eytan (Quarterly Journal of Economics, 1978)
I. Introduction, 589. — II. An optimal negative income tax model, 591. — III. The maximin criterion, 594. — IV. A utilitarian social objective, 597. — V. Conclusion, 598. Our theory … depends upon the validity of a single hypothesis, viz.: that the utility index is a function of relative rather than absolute consumption expenditure. — J. Duesenberry Income, Saving and the Theory of Consumer Behavior